Pengembangan Modul Creative Problem Solving (CPS) untuk Meningkatkan Keterampilan berpikir kreatif dan Self-efficacy Peserta didik SMP - Muhammad Awaluddin Fitri; Sutarto Hadi; Arif Sholahuddin; Rusmansyah Rusmansyah; Mohamad Nor Aufa; Muhammad Hasbie; Muhammad Aditya Saputra (Jurnal Penelitian Pendidikan IPA, 2023)
This research was conducted on the existence of problems in the form of low creative thinking skills and students' self-efficacy in learning. One way that can be done to solve this problem is by utilizing teaching materials in the form of modules that students can use for independent learning. Therefore, this research was conducted to develop science learning modules to improve the creative thinking skills and self-efficacy of class VIII students of junior high school. This type of research is Educational Design Research (EDR) using the Tessmer development model. The final result of the validation average is 3.49, which is in the very valid category. Therefore, based on the research results, the science learning module has been declared very valid to improve students' creative thinking skills and self-efficacy in learning science